Social, Psychological, and Emotional: Autism Children Factors by Case Study within Face to Face Approach - Satrianawati, Satrianawati (International Journal of Active Learning, 2018)
The problem of many autism children in Yogyakarta. With an overall ratio of approximately 11 children to 43 students, there is a substantial quantity of autism. However, these are many children with special needs. Autisms is commonly disordering seriously. This condition creates abnormal repeatedly of DNA basis sequence to chromosome X so impair that one gene is known by inheritance mum to the baby. The method is qualitative approached using case study within social, psychological, and emotional factors. Collected data by interview, participant observations, and documentation. The object is an autism student in Mrisi Muhammadiyah Elementary school. The result showed that there are three factors causing autism students, such is social, psychological, and emotional.